PENGARUH PUPUK HAYATI PADAT TERHADAP SERAPAN N DAN P TANAMAN, KOMPONEN HASIL DAN HASIL PADI SAWAH (Oryza sativa L.) - Mieke Rochimi Setiawati; Emma Trinurani Sofyan; Zaenal Mutaqin (Jurnal Agroekoteknologi, 2016)
Optimization of production rice plants can be achieved if the needs of macro and micro nutrients essential plant fulfilled. To achieve optimal rice yield can be done by proper fertilization based on the type, characteristics and nutrient content of fertilizers applied. Alternative to increasing rice yield can be done by applying biofertilizer in reducing the use of inorganic fertilizers. This experiment aims to determine the effect of Solid Biofertilizer (SBF) on nutrient uptake, growth, and yield and yield components of rice paddy fields. This research was carried out on the planting medium Inceptisols at Jatinangor used a Randomized Completely Block Design (RCBD) with 10 treatment combinations which replicated 3 times. The results showed that a dose of 1 NPK, combined with SBF ranging from ¼ dose, dose ½, ¾ and 1-dose showed gradual improvement to the uptake of N and P as well as yield and yield components of paddy.Keywords: Solid Biofertilizer, NPK Fertilizer, Paddy Yield